Redox-Driven mineral formation mediated by imogolite nanotubes: Experimental and DFT insights into Fe2+ oxidation under variable oxygen conditions - R.D. Cuevas-Alfaro; José D. Fabris; José D. Ardisson; Carmen Pizarro; Helio A. Duarte; Lisa Muñoz; Leidy Orozco; Karen Manquián-Cerda; Nicolás Arancibia-Miranda (Applied Clay Science, 2026)

Gully erosion assessment in mountainous regions: a RUSLE-based methodology for the Central Peruvian Andes - Clifton Paucar-Y-Montenegro; Miluska A. Rosas; Ada Arancibia (Hydrological Sciences Journal, 2026)

Culture conditions shape metabolism and exopolysaccharide production in Piscirickettsia salmonis: implications for vaccine development - Patricio A. Zelada-Cordero; Claudia Altamirano; Alejandra Arancibia-Diaz; Carla L. Gutiérrez; Norma A. Valdez-Cruz; Mauricio A. Trujillo-Roldán (Aquaculture International, 2025)
Piscirickettsia salmonis is the primary bacterial pathogen affecting Chilean salmon farming, resulting in annual economic losses of approximately US$700 million. The limited effectiveness of antibiotics and current vaccines underscores the need to enhance upstream cultivation strategies for producing biomass suitable for vaccine production. In this study, two shake flask designs—baffled (BF) and standard non-baffled (NF)—were compared to evaluate how differences in mass and momentum transfer impact the metabolic activity and physiological behavior of P. salmonis under axenic, submerged batch conditions. Despite a 2.5-fold increase in oxygen transfer in BF flasks, the results indicated that this configuration had a negative impact on bacterial performance. Specific growth rates were reduced by 22–39%, and volumetric productivity decreased by 23% compared to NF. Glutamate was fully consumed in NF but remained partially unused in BF, indicating a reduced uptake under shear or oxidative stress. Respiratory activity also differed: NF cultures exhibited distinct peaks in oxygen transfer rate during growth, while BF cultures showed flatter, more constant profiles. Importantly, exopolysaccharide (EPS) production, a trait associated with virulence and immunogenicity, was over fivefold higher in NF (1.48 g/L) than in BF (0.27 g/L). These findings demonstrate that the physical conditions imposed by flask design have a significant influence on P. salmonis growth, respiration, and EPS output. Adjusting cultivation conditions at this early stage can enhance the consistency and quality of biomass used in bacterin-based vaccines. This approach provides a practical tool to improve upstream standardization and supports the development of more effective control strategies for piscirickettsiosis in the aquaculture industry.

Two Decades of Community Responses Reveal a Consistent Increase in Species Occurrences in South‐Eastern Pacific Rocky Shores - Mauricio H. Oróstica; Paulina A. Arancibia; Otso Ovaskainen; Sergio A. Navarrete; Bernardo R. Broitman (Global Ecology and Biogeography, 2025)
Aim Understanding how diverse communities respond to environmental fluctuations is a central challenge in ecology. Here, we assessed how communities responded to environmental variation over the past 23 years and evaluated the extent to which these responses can be associated with taxonomic relationships, as well as biological and ecological species traits. Location Central portion of the Humboldt Upwelling Ecosystem, with 22 rocky shore survey sites spanning 8° of latitude (28° S–36° S). Time Period 2000–2023. Major Taxa Studied Intertidal zone communities. Methods We used joint species distribution models to integrate quantitative survey data, satellite sea surface temperature (SST) as a proxy for environmental conditions, taxonomic information and species biological traits along a latitudinal gradient with heterogeneous thermal conditions. Results Our proxy for environmental variation revealed weak and non‐significant SST cooling at central sites, whereas sites near 30° S showed slight warming trends. Taxonomic relationships and individual species traits were weakly associated with their collective responses to SST variability. However, we identified a consistent increase in the occurrence of both macroalgal and invertebrate species across the region. The occurrence of macroalgal species was more sensitive to SST variation than invertebrates, with responses shifting from positive at equatorward sites to increasingly negative at poleward sites. Patterns of species co‐occurrence were strongly dependent on spatial scale, particularly among invertebrates. Main Conclusions Species occurrences increased across the region, but these responses were not significantly associated with taxonomic relatedness or with easily assigned species traits. This pattern likely indicates comparatively low niche conservatism within these communities in relation to SST responses, while other structuring processes—such as species interactions—are not well captured by the traits examined. As other studies have detected slight cooling trends over the past two decades, our results suggest that the lack of community‐wide reorganisation reflects the absence of a clear environmental driver.

Advanced Zeolite Composites with nZVI for Lead Removal in Mining Water: Laboratory Results and Field Validation - Tamara Maldonado; Karen Manquián-Cerda; Isadora Fuentealba; Raúl Calderón; María A. Rubio; Alejandra García; Nicolás Arancibia-Miranda (Water, Air, & Soil Pollution, 2025)

Molecular identification, risk factors’ assessment and phylogenetic analysis of Toxoplasma gondii in goats from Malakand Division, Khyber Pakhtunkhwa, Pakistan - Ahmad Irshad; Shumaila Noreen; Uswa Sajid; Muhsin Jamal; Muhammad Anwar Iqbal; Ubaid Ullah; Talat Sabtain; Shakir Ullah; Eliana Ibañez-Arancibia; Patricio R. De Los Ríos-Escalante; Hanène Belkahia; Mourad Ben Said; et al. (Veterinary Research Communications, 2025)

Urbanization's hidden influence: Linking landscape alterations and feather coloration with pigeon's cholesterol levels - Javiera Arcila; Isaac Peña-Villalobos; Catalina B. Muñoz-Pacheco; Felipe Sanhueza-Cisterna; Daniela Galdames; David Arancibia-Altamirano; Fabiola A. Otárola; Diego Landaeta; Francisco del Basto; Carolina Cárdenas Aroca; Tomás Jiménez; Pablo Sabat; et al. (Environmental Research, 2025)

Wind Is a Primary Driver of Fungal Dispersal Across a Mainland‐Island System - D. Naranjo‐Orrico; O. Ovaskainen; B. Furneaux; J. Purhonen; P. A. Arancibia; S. Burg; N. Moser; J. Niku; G. Tikhonov; E. Zakharov; N. Monkhouse; N. Abrego (Molecular Ecology, 2025)
Dispersal is one of the main processes shaping ecological communities. Yet, for species‐rich communities in natural systems, the role of dispersal in community assembly remains relatively less studied compared to other processes. This is the case for fungal communities, for which predictable knowledge about where and how the dispersal propagules move across space is largely lacking. We sampled fungal communities at their dispersal stage in a lake mainland‐island system in Finland, using a regular grid of 18 × 18 km, including sites on the mainland, islands and over the water. Fungal communities were screened by applying DNA barcoding to air samples. To assess the factors determining fungal dispersal, we modelled aerial fungal communities with a joint species distribution model, including spore traits, weather‐related predictors, and spatial predictors. We found that the probability of occurrence of most species (and consequently species richness measured as the number of OTUs per sample) was lower in low‐connectivity sites (water and isolated islands) compared to high‐connectivity sites (mainland). There was a strong phylogenetic signal in how the fungal species responded to connectivity, indicating that some taxonomic groups are more dispersal limited than others, although such responses were not structured by their trophic guilds. Furthermore, wind speed influenced how species with different spore sizes responded to connectivity: in low‐connectivity sites, species with large sexual spores were detected especially when wind was high, whereas, in high‐connectivity sites, they were detected especially when wind was low. This study demonstrates that air fungal dispersal might be more predictable than previously considered and contributes to the mechanistic understanding of fungal air dispersal.

Potential of mesenchymal stromal/stem cells and spermatogonial stem cells for survival and colonization in bull recipient testes after allogenic transplantation - Moisés N. Segunda; Jahaira Cortez; Carlos Díaz; Richard Arancibia; Cristian G. Torres; Víctor H. Parraguez; Mónica De los Reyes; Oscar A. Peralta (Theriogenology, 2024)

Optimizing flotation circuits: A comprehensive approach using design of experiments and stochastic simulation in cycle test validation - Felipe D. Sepúlveda; Lorena A. Cortes; María P. Arancibia-Bravo; José Delgado; Freddy A. Lucay; Carlos Chacana; Felipe Galleguillos; Cesar Castellón (Minerals Engineering, 2024)

Integrating the enzymatic syntheses of lactulose, epilactose and galacto-oligosaccharides - Macarena Huerta; Andrea San Martín; Benjamín Arancibia; Fabián A. Cornejo; Felipe Arenas; Andrés Illanes; Cecilia Guerrero; Carlos Vera (Food and Bioproducts Processing, 2024)

Non-indigenous species and their realized niche in tidepools along the South-East Pacific coast - David Jofré-Madariaga; Moisés A. Aguilera Moya; Catharina Alves-de-Souza; Rene Matías Arias; Lars Gutow; Ricardo Antonio Jeldres Polanco; Erasmo C. Macaya; Martín Munizaga Kappes; Leslie Nicole Ortiz Arancibia; Oscar Pino; Sabine Rech; Eva Rothäusler; et al. (Marine Environmental Research, 2024)

Environmentally friendly process for phytosterols recovery from residues of biodiesel production. - Renzo Carlucci; Juan A. Arancibia; Guillermo R. Labadie (Sustainable Chemistry and Pharmacy, 2024)

Prenatal caloric restriction adjusts the energy homeostasis and behavior in response to acute and chronic variations in food availability in adulthood - Isaac Peña-Villalobos; Fabiola A. Otarola; David Arancibia; Pablo Sabat; Verónica Palma (Journal of Comparative Physiology B, 2023)

A new constraint to model background signals when processing chromatographic-spectral second-order data with multivariate curve resolution - Maira D. Carabajal; Rocío Pellegrino Vidal; Juan A. Arancibia; Alejandro C. Olivieri (Analytica Chimica Acta, 2023)

Stomach contents and stable isotope analysis reveal ontogenetic shifts and spatial variability in Brama australis diet - Sebastian A. Klarian; Eric T. Schultz; María Francisca Hernández; Juan Antonio Valdes; Francisco Fernandoy; Mónica E. Barros; Sergio Neira; Hugo Arancibia (Environmental Biology of Fishes, 2022)

Juvenile Hake Merluccius gayi Spatiotemporal Expansion and Adult-Juvenile Relationships in Chile - Daniela V. Yepsen; Luis A. Cubillos; Hugo Arancibia (Fishes, 2022)
The abundance of juvenile fish changes due to endogenous processes, and determining the functional relationships among conspecifics is essential for fisheries’ management. The hake (Merluccius gayi) is an overexploited demersal fish widely distributed in Chile, from 23°39′ S to 47°00′ S in shallow and deep water over the continental shelf and shelf break. We studied the spatiotemporal distribution of hake juveniles (from ages 0 and 1), emphasizing endogenous relationships among juveniles and adults. The abundance per age data were obtained from bottom trawl cruises carried out in the austral winter between 1997 and 2018. Generalized additive models showed a similar spatiotemporal pattern for ages between 0 and 1, and negative effects of adult hake aged seven and older on the abundance of the young generation. Regarding the changes in juvenile abundance, the residual deviance of selected models explained 75.9% (for the age 0) and 95.3% (for the age 1) of the null deviance, revealing a significant increase in juvenile abundance from 2002 to 2007 and subsequent abundance stability at higher levels. Furthermore, the expansion in the abundance of juveniles after 2002 was favored by the low abundance of older adult hake, most which are able to cannibalize young hake. Our results highlight the importance of endogenous factors in the spatial distribution of Chilean hake juveniles to identify nurseries or juvenile areas free of potential cannibal adults.

The Exocyst Component Exo70 Modulates Dendrite Arbor Formation, Synapse Density, and Spine Maturation in Primary Hippocampal Neurons - Matías Lira; Duxan Arancibia; Patricio R. Orrego; Carolina Montenegro-Venegas; Yocelin Cruz; Jonathan García; Sergio Leal-Ortiz; Juan A. Godoy; Eckart D. Gundelfinger; Nibaldo C. Inestrosa; Craig C. Garner; Pedro Zamorano; et al. (Molecular Neurobiology, 2019)

Do your gut microbes affect your brain dopamine? - Camila González-Arancibia; Jocelyn Urrutia-Piñones; Javiera Illanes-González; Jonathan Martinez-Pinto; Ramón Sotomayor-Zárate; Marcela Julio-Pieper; Javier A. Bravo (Psychopharmacology, 2019)

Tectono-metallogenetic evolution of the Fe–Cu deposit of Dominga, northern Chile - E. Veloso; J. Cembrano; G. Arancibia; G. Heuser; S. Neira; A. Siña; I. Garrido; P. Vermeesch; D. Selby (Mineralium Deposita, 2017)

Productivity of a Continuous Mining System for Block Caving Mines - L. F. Orellana; R. Castro; A. Hekmat; E. Arancibia (Rock Mechanics and Rock Engineering, 2017)

Coleoptera Associated with Decaying Wood in a Tropical Deciduous Forest - N Z Muñoz-López; A R Andrés-Hernández; H Carrillo-Ruiz; S P Rivas-Arancibia (Neotropical Entomology, 2016)

The environmental legacy of the Ixtoc-I oil spill in Campeche Sound, southwestern Gulf of Mexico - Luis A. Soto; Alfonso V. Botello; Sergio Licea-Durán; Marcial L. Lizárraga-Partida; Alejandro Yáñez-Arancibia (Frontiers in Marine Science, 2014)

Influence of 5-chloro and 5-methyl benzotriazole on the corrosion of copper in acid solution: an experimental and a theoretical approach - A. Arancibia; J. Henriquez-Roman; M. A. Páez; L. Padilla-Campos; J. H. Zagal; J. Costamagna; G. Cárdenas-Jirón (Biotechnology Letters, 2005)